Water as weapon: IS on the Euphrates and Tigris. The systematic instrumentalisation of water entails conflicting IS objectives - Tobias von Lossow (Stiftung Wissenschaft und Politik (SWP), 2016)
In the course of its territorial expansion, Islamic State (IS, ISIL or ISIS) has brought under its control strategically significant water resources and large parts of the water infrastructure in Syria and Iraq. It has seized several important dams on the Euphrates and Tigris as part of its expansion strategy and, particularly since 2014, has used water as a weapon in a number of ways. This practice has disastrous consequences, and it is virtually impossible for external actors to prevent it. And yet, even IS's room for manoeuvre is limited since a functioning water and electricity supply in the areas that it has captured is of existential importance for the militia. However, the anti-IS coalition's intensified military interventions since the Paris attacks put the militia under severe pressure. Should IS be forced into extensive withdrawals, then whole regions will be at risk of dramatic and wide-spread flooding. (SWP Comments)
Keywords: 320